Incidence of hypocalcaemia among post-thyroidectomy patients at a tertiary care hospital at Trivandrum, Kerala, South India - Thottath, Deepu; Babu, Dayananda; Thangavel, Saravanan; Kannan, Radhika (International Surgery Journal, 2021)
Background: Hypocalcemia is one of the most common complications of thyroid surgery. It is usually temporary, but it may rarely take several months to resolve. The aim of this study was to determine the incidence of hypocalcaemia after total thyroidectomy and assess the biochemical factors that may be predictive of hypocalcemia. Methods: An observational study was conducted in 98 patients at the general surgery department of a tertiary care medical college hospital for a period of one year. Convenient method of sampling was done. All the patients undergoing total thyroidectomy were included in this study. The serum calcium level was evaluated at different times in the post-operative period as a part of the routine post-operative care at the hospital. During the postoperative period patients were carefully watched for clinical symptoms and signs of hypocalcemia. Results: In the study group, 19 (19.4%) had hypocalcemia. In the study group, 14 (14.3%) had symptomatic hypocalcemia and 5 patients (5.1%) had asymptomatic hypocalcemia. 18 patients (18.4%) had temporary hypocalcemia and 1 patient (1%) had permanent hypocalcemia. Among the patients with hypocalcemia, 18 (95%) were females and 1 (5%) patient was male. 13 (68%) patients were euthyroid, 5 (26%) patients were hyperthyroid and 1 (5%) patient was hypothyroid. Significant association was seen between diagnosis of thyroid disorders and hypocalcemia, thyroid function and hypocalcemia and between operating time and hypocalcemia. Conclusions: Incidence of hypocalcemia in patients who had undergone total thyroidectomy was found to be less. Majority of them had temporary hypocalcemia and permanent hypocalcemia was seen only in one patient.